2019
DOI: 10.1155/2019/6360459
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes as an Early Predictor for Patients with Acute Paraquat Poisoning: A Retrospective Analysis

Abstract: Background. The predictive values of monocytes in the prognosis of patients with acute paraquat (PQ) poisoning are unclear. This retrospective study investigated the predictive values of monocytes in the prognosis of patients with acute PQ poisoning. Methods. Adult patients who suffered from acute PQ poisoning in the emergency care unit of Cangzhou Central Hospital from May 2012 to December 2018 were enrolled. The patients were divided into groups, namely, survival and nonsurvival, according to a 90-day progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
9
0
2
Order By: Relevance
“…The neutrophilic granulocyte ratio and leukocyte count reflect the immune status of the body. Several studies have shown that the immune system of patients was activated during the paraquat poisoning [ 9 , 10 ]. As expected, the neutrophilic granulocyte ratio and leukocyte count increased in both survivors and nonsurvivors ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophilic granulocyte ratio and leukocyte count reflect the immune status of the body. Several studies have shown that the immune system of patients was activated during the paraquat poisoning [ 9 , 10 ]. As expected, the neutrophilic granulocyte ratio and leukocyte count increased in both survivors and nonsurvivors ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early renal dysfunction indicates severe disease and poor prognosis. Renal function is a key parameter in clinical practice to determine prognosis of PQ poisoning (Lee et al, 2002;Weng et al, 2017;Zhao et al, 2019). Some studies have pointed to urinary PQ as the most valuable indicator in estimating severity and prognosis at the time of admission (Liu et al, 2017b;Tan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We performed a 10-year, observational, retrospective analysis of all patients who were admitted to our hospital after drinking PQ pesticide and who had already been discharged from hospital or had died from 1 January 2009 to 31 December 2018. 12 All patients were admitted to the hospital in accordance with standard medical emergency procedures. 13 …”
Section: Methodsmentioning
confidence: 99%
“…Patients with acute PQ poisoning usually die within a few weeks after PQ ingestion. 12 Therefore, an effective treatment was described as patients who survived more than 3 months after PQ poisoning, had stable vital signs, and had no evidence of progressive organ failure (especially the kidneys and lungs). 13 We also determined survival using medical records or telephone follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation